Pengaruh Penerapan Model Discovery Learning terhadap Pemahaman Konsep Matematika Peserta Didik Kelas VIII SMPN 4 Pariaman - FINA MASHLAHATUL MAZZA (Jurnal Edukasi dan Penelitian Matematika, 2020)
Mathematical concept understanding must be owned by students as the basic ability of learning mathematics. But, the fact showed that  students’ mathematical concept understanding of  eighth graders SMPN 4 Pariaman were low. According to observation result, learning implementation tended to be teacher center, so they were not involved actively in learning activity. The effort to solve this problem was implementing discovery learning model as a place to train them constructing their own mathematical concept understanding. The goal of  this research was to compare the difference between mathematical concept of students who learned by discovery learning model and who learned conventional learning. The type of research was quasy experiment with static group design. Based on hypothesis result that mathematical concept understanding of students who learn by using discovery model is better than who learn by using conventional learning. Therefore, it can be concluded that discovery learning model affects on mathematical concept understanding. Keywords — Discovery Learning Model, Mathematical Concept Understanding.